DRUG INDUCED NEUROPATHY - Anisa Syahfitri Hanum; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Neuropathy is a painful condition and originates from a variety of etiologies. Many drugs can cause neuropathy, which is known as Drug-Induced Neuropathy (DIN), which is included in iatrogenic cases. These drugs are chemotherapy agents, antimicrobials, cardiovascular drugs, psychotropics, anticonvulsants, etc. Not all neuropathies require pharmacological therapy, but simply stop therapy, and the complaints will improve (reversible). However, there are quite a few DINs with a “coasting